Variational Retinex model based on an extension of TV regularization with relative gradient and its application - Ning ZHI; Shan-jun MAO; Mei LI (Tongxin xuebao, 2017)
In view of the shortcomings of the total variational Retinex model which use the total variation (TV) of the reflection as the regularization.An extension of TV regularization with the concept of relative gradient was introduced and finally a new variational Retinex model was proposed.Compared with variational Retinex and total variational Retinex model,the proposed model can preserve the estimated reflectance with more details as well as the more smoothed illumination.Further,a new integrated image enhancement model considering both the illumination and the reflectance was proposed.By adjusting the model parameters,the proposed model can be effectively applied to high dynamic range image tone mapping and non-uniform illumination enhancement.Compared with other algorithms,the proposed model can better handle the above image enhancement problems.